2015
DOI: 10.1007/s10482-015-0417-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the iac locus from Acinetobacter baumannii by the phytohormone indole-3-acetic acid

Abstract: The iac locus is involved in indole-3-acetic acid (IAA) catabolism in Acinetobacter baumannii. Nine structural genes of iac are transcribed in the same direction, whereas iacR, which encodes a MarR-type transcriptional regulator, is transcribed in the opposite direction. The IacA protein, which is encoded by the second structural gene of the iac locus, is expressed in an IAA-dependent manner. Here, we characterized gene expression from this locus in wild type A. baumannii and in an iacR mutant; this revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Comparisons between iac homologues showed amino acid identities ranging from 38 to 62% (see Table S1 in the supplemental material). Only the iacR gene strain 1290 homologue, a transcriptional repressor belonging to the MarR family (14,15), is absent in the strain PsJN genome. The strain PsJN iac gene sequences are adjacent to other genes, not found in P. putida 1290, possibly playing regulatory and transport roles in IAA degradation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparisons between iac homologues showed amino acid identities ranging from 38 to 62% (see Table S1 in the supplemental material). Only the iacR gene strain 1290 homologue, a transcriptional repressor belonging to the MarR family (14,15), is absent in the strain PsJN genome. The strain PsJN iac gene sequences are adjacent to other genes, not found in P. putida 1290, possibly playing regulatory and transport roles in IAA degradation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IAA degradation by strain PsJN apparently uses some functionally redundant genes and other genes not previously reported in P. putida 1290, encoding transport and tautomerase superfamily enzymes. We also reported that, in contrast with P. putida and A. baumannii, where iac gene regulation is controlled by a MarR-type transcriptional repressor responding to the IAA molecule (14,15), IAA degradation in P. phytofirmans is regulated by a two-component system and a LysR-type activator, which apparently respond to IAA in combination with DOAA, the previously proposed intermediate in strain 1290 (14).…”
mentioning
confidence: 81%
See 3 more Smart Citations